The Contribution of Mental Toughness Towards Competitive Anxiety in U-15 Football Athletes of SSB Tunas Inti Kota Sungai Padang: Artikel - Algipari, Muhammad; Susanto, Nugroho (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research aims to find out how much mental toughness contributes to competitive anxiety behavior in athletes. This research is quantitative research with a descriptive type with statistics used to analyze data by describing or illustrating the data that has been collected. Variable X is mental toughness and variable Y is competitive anxiety. The population in this study were SSB Tunas Inti FC U-15 athletes in Sungai Banyak City. The sampling technique uses purposive sampling. The instruments used in this research use two types of scales, namely the mental toughness scale and the competitive anxiety scale, both of which will be modified using a Likert scale. This analysis was carried out using statistical tests, namely correlation and determination tests which were processed using the SPSS version 29.0 program. The results of the correlation analysis of the relationship between mental toughness and competitive anxiety show that the p value < 0.001 < is smaller than 0.05, indicating that there is a significant negative relationship between mental toughness attitude and competitive anxiety behavior and the results of the determination test obtained a coefficient of determination percentage of 66.2%. shows that there is a significant positive contribution of mental toughness attitude to competitive anxiety. So athletes need to improve their mental toughness attitude in order to reduce competitive anxiety behavior, and coaches can facilitate and support them to increase their mental toughness attitude.